2012
DOI: 10.1017/s0021859612000615
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for quantifying gastrointestinal nutrient absorption and metabolism in a native and a modern pig breed

Abstract: When working with multi-catheterized animals, success and failure are separated by surgical procedures and minor details in catheter design and care. The current paper is a detailed description of novel approaches to multicatheterization of pigs for investigations into nutrient absorption and metabolism of portal-drained viscera (PDV) in a native obese (Iberian) and a modern (Landrace) breed. Three Iberian and three Landrace gilts (25 kg average body weight; BW) were fitted with catheters in the carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
4
12
1
Order By: Relevance
“…Anderson et al pointed out that in pigs the haematocrit value was variable. Nonetheless, in previous studies also with Iberian pigs, similar values to those in the present study were found, ranging from 30 to 31% . The haematocrit value was higher in Iberian than in improved breeds, although some authors reported similar values in modern breeds to those reported herein …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Anderson et al pointed out that in pigs the haematocrit value was variable. Nonetheless, in previous studies also with Iberian pigs, similar values to those in the present study were found, ranging from 30 to 31% . The haematocrit value was higher in Iberian than in improved breeds, although some authors reported similar values in modern breeds to those reported herein …”
Section: Discussionsupporting
confidence: 91%
“…Feed was offered at 0.3, 0.6 and 1 of the daily ration on days 1, 2 and 3 post‐surgery respectively, with free access to water. A detailed description of the catheter design, construction and maintenance, surgical procedure and post‐surgery care of pigs was published elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported after conventional catheterization, ranging from 6 to 12 wk (Yen and Killefer 1987;Leeuwen et al 1995;Hooda et al 2009;Rodríguez-lópez et al 2013). Occlusion of implanted catheters is a common problem in multicatheterized pigs used for studies.…”
Section: Discussionsupporting
confidence: 80%
“…Further, the adhesions should be strong so as to avoid kinking of the catheter. We believe that this laparoscopic procedure reduces surgical stress to previous studies (Yen and Killefer 1987;Henry et al 2010;Rodríguez-lópez et al 2013) and minimizes the chances of catheter dislodgement and a function, both of which are benefit to the long-term metabolic assessment of the animal model.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation